The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/1440-1681.13624
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the protective face mask on cardiorespiratory response during aerobic exercise

Abstract: The protective face mask (PFM) has been widely used for safety purposes and, after the advent of the COVID‐19 pandemic, its use is growing steadily, not only among healthcare personnel but also the general population. While the PFM is important to preserve the wearer from contaminating agents present in the airflow, they are well known to increase the subjective perception of breathing difficulty. Although some studies have demonstrated that PFM use worsens exercise tolerance, several studies state that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
0
12
0
3
Order By: Relevance
“…In contrast, a systematic review of the literature and meta-analysis showed that wearing a facemask while exercising had no impact on exercise performance ( Shaw et al, 2021b ). This contradiction may be due to the type of mask worn and the exercise practiced ( do Prado et al, 2022 ; Fikenzer et al, 2020 ). In addition, considering that cardiovascular fitness is strongly correlated to cognition ( Hötting and Röder, 2013 ) as well as exercise and physical activity in general ( Mandolesi et al, 2018 ), it is important to evaluate the impact of exercising while wearing a facemask on cognitive functioning.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a systematic review of the literature and meta-analysis showed that wearing a facemask while exercising had no impact on exercise performance ( Shaw et al, 2021b ). This contradiction may be due to the type of mask worn and the exercise practiced ( do Prado et al, 2022 ; Fikenzer et al, 2020 ). In addition, considering that cardiovascular fitness is strongly correlated to cognition ( Hötting and Röder, 2013 ) as well as exercise and physical activity in general ( Mandolesi et al, 2018 ), it is important to evaluate the impact of exercising while wearing a facemask on cognitive functioning.…”
Section: Introductionmentioning
confidence: 99%
“…• The effect of the protective face mask on cardiorespiratory response during aerobic exercise , Prado DML et al, 2021 [10] • Six-minute walk test as a resource for prescribing high-intensity physical training for patients with chronic obstructive pulmonary disease , Rodrigues ALL., 2016 [27] • Building a new concept in metabolic studies in exercise science , Bassani A, Cameron LC, 2014 [9] • Immediate effects of whole-body vibration exercise on hemodynamic, hormonal parameters and oxidative biomarkers in sarcopenic elderly: a randomized controlled clinical trial , Paula FA de, 2021 [26] Transdisciplinary teams 3 • Effect of sports training on residents of areas of social vulnerability: a study using heart rate variability (HRV) and biofeedback , Silva Junior RM da, 2020 [16] 1. Publication of the largest number of national studies.…”
Section: Area N Articlesmentioning
confidence: 99%
“…In Brazil, the Paulista Society of Sports Medicine (SPAMDE) was founded in 1942, and the Brazilian Federation of Exercise and Sports Medicine, which later became the Society of Exercise and Sports Medicine, was founded in 1962 (SMBEE). It should be noted that, despite technological advances in the field, this medical specialty is still relatively new; it first appeared in Sao Paulo at the end of the 1930s to verify the absence of diseases in athletes, sparking interest in the effect of physical activity and sport on health and thus strengthening the sport and health binomial [10] .…”
Section: Introductionmentioning
confidence: 99%
“…After years of experimental observation in academia, it has been found that better endurance is the fundamental guarantee for winning the game. 1 Low stamina is the main reason for the failure of the vast majority of players. Correctly looking at and solving the endurance in basketball is related to whether the level of modern basketball can be further improved.…”
Section: Introductionmentioning
confidence: 99%